Digital Humanities in biblical, early Jewish and early Christian studies - Clivaz, Claire; Gregory, Andrew F.; Hamidovič, David; Schulthess, Sara. (Leiden : Brill, 2014)
Ancient texts, once written by hand on parchment and papyrus, are now increasingly discoverable online in newly digitized editions, and their readers now work online as well as in traditional libraries. So what does this mean for how scholars may now engage with these texts, and for how the disciplines of biblical, Jewish and Christian studies might develop? These are the questions that contributors to this volume address. Subjects discussed include textual criticism, palaeography, philology, the nature of ancient monotheism, and how new tools and resources such as blogs, wikis, databases and digital publications may transform the ways in which contemporary scholars engage with historical sources.
List of Contributors; List of Abstracts; Preface; Introduction: Digital Humanities in Biblical, Early Jewish and Early Christian Studies; Part One Digitized Manuscripts; The Leon Levy Dead Sea Scrolls Digital Library. The Digitization Project of the Dead Sea Scrolls; Dead Sea Scrolls inside Digital Humanities. A Sample; The Electronic Scriptorium: Markup for New Testament Manuscripts; Digital Arabic Gospels Corpus; The Role of the Internet in New Testament Textual Criticism: The Example of the Arabic Manuscripts of the New Testament.
Includes bibliographical references and indexes.
Print version record.
Keywords: Bible -- Criticism, Textual; Bible -- Study and teaching -- Research -- Methodology; Humanities -- Electronic information resources; Humanities -- Computer network resources; Communication in learning and scholarship -- Technological innovations; Scholars -- Effect of technological innovations on; Manuscripts -- Digitization; Jews -- Study and teaching -- Research -- Methodology; Christians -- Study and teaching -- Research -- Methodology; Philology -- Research -- Methodology; Paleography -- Research -- Methodology; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Electronic books; Electronic books